PENGARUH MODEL PEMBELAJARAN INQUIRY TERHADAP KEMANDIRIAN BELAJAR MAHASISWA - Yunus, Muh. Rizal Kurniawan; Irawan, Ferry (Jurnal Biogenerasi, 2023)
In the implementation of higher education, building student independence in learning is an important part. In a higher education environment, students who can study independently will be better prepared to face changes in the dynamic and fast world of work. Development of student learning independence can be done by choosing a learning model that develops students' thinking skills and self-confidence. One way is to apply the inquiry learning model which is a learning model that is oriented towards students' ability to build their knowledge independently. This study aims to determine the effect of the inquiry learning model on student learning independence in the biology education study program at the University of West Sulawesi. This type of research is quasi-experimental research. This research was carried out in the odd semester of the 2022/2023 school year with a population of all fifth-semester students who programmed the Learning Innovation course by taking samples using a purposive sampling technique so that class A and class B became the research sample with a total of 58 students. The instrument used in this study was a learning independence questionnaire consisting of 5 indicators and 20 questions. Data analysis was carried out using descriptive analysis to determine the increase in the value of student learning independence and inferential analysis to test the hypothesis using the Anacova test. The results of the hypothesis test using Anacova obtained a significance value of 0.001 <0.05 so it can be said that H0 is rejected and H1 is accepted which means that there is an influence of the application of the inquiry learning model on the learning independence of students in the Biology Education Study Program, Universitas Sulawesi Barat